EFEKTIVITAS PELATIHAN KOMUNIKASI POSITIF TERHADAP KEMAMPUAN KOMUNIKASI POSITIF GURU DI TK IT TOP KIDS SOKARAJA PURWOKERTO - Hapsari Melati Ismi; Yuki Widiasari (Khazanah Pendidikan, 2018)
This study aims to improve Master's positive communication skills in early childhood.Subjects in this study were 12 teachers in PAUD Top Kids Sokaraja district. Theresearch was conducted through experimental method. Subjects were subjected to twopositive meetings of positive communication training, with the total number ofmeetings being 8 hours. Data analysis was done by visual inspection technique, on 4measurement of baseline stage, treatment stage 1, treatment stage 2, and follow-upstage. The results of the study prove a significant increase in the positivecommunication skills of the subject, based on the scale of positive communicationskills. In the baseline phase, the average subject has a positive communication skillscore of 33.67 (Enough). In the treatment phase 1, it increased to 38.08 (Enough). Inthe third measurement, ie in the treatment phase 2, increased to 44.41 (Good). In thefollow-up phase it increased to 48.08 (Good).Keywords: positive communication skills, communication training, kindergartenteacher